Efficacy and safety of thermal ablation for Bethesda III/IV thyroid nodules: a retrospective study - Li, Song; Wei, Ying; Zhao, Zhen-long; Peng, Li-li; Li, Yan; Yu, Ming-an (Frontiers in Endocrinology, 2025)
ObjectivesTo evaluate the efficacy and safety of thermal ablation (TA) for the treatment of Bethesda III and IV thyroid nodules.Materials and methodsA retrospective analysis was conducted on 154 patients with Bethesda III (n = 82) and IV (n = 72) thyroid nodules treated with microwave or radiofrequency ablation between December 2016 and October 2023. Patients were followed for a median of 19 months. Outcomes assessed included nodule volume reduction rate (VRR), complications, and disease progression.ResultsThe median VRR at 12 months was 97% (Bethesda III) and 88% (Bethesda IV), increasing to 100% and 96% by 36 months, respectively, with no significant differences between groups. No major complications were encountered, minor complications occurred in 4 patients (4/154, 2.6%), including 3 cases of transient hoarseness and 1 case of neck pain, resolving spontaneously. Disease progression (3/154, 1.9%) occurred in both groups, with new tumor in each group, no other disease progression occurred.ConclusionThermal ablation could be a safe, effective, and minimally invasive alternative to surgery for Bethesda III/IV thyroid nodules, achieving substantial volume reduction with minimal complications.